(untitled) (LACCEI, 2024)
The pandemic confronted all Peruvians to assume challenges facing the health situation and the changes that emerge from the current globalization, many of the businesses could not be sustained and closed, others changed their line of business and several had to redirect to continue working, however the Peruvian is characterized by being enterprising, ingenious and industrious and so began to use digitization to undertake and make their businesses a new way to deal with the situation that was living and that still affects the economy of all citizens Several of the university students eager to put into practice their knowledge and be able to help in the economy of their homes, have launched their digital entrepreneurship skills, which is why the purpose of the study was to determine the relationship between lifestyles and digital entrepreneurship of university students in Trujillo in times of pandemic 2022, and thus be a reference for the new generations. The methodology used was of causal correlational scope and its design was non-experimental, cross-sectional, correlational. The survey technique was used. The results indicate that there is a direct and significant relationship between the variable Lifestyles and Digital Entrepreneurship Competences with a value of Spearman’s correlation coefficient, rho=0.82, and this relationship indicates that the better the lifestyle, the higher the level of digital competences, because the students show a better predisposition to achieve their goals.